1996
DOI: 10.1111/j.1439-0418.1996.tb01620.x
|View full text |Cite
|
Sign up to set email alerts
|

The predation of Chrysoperla carnea (Neurop., Chrysopidae) on eggs and larvae of Mamestra brassicae (Lep., Noctuidae)

Abstract: In the present study the predation rate of Chrysoperla carnea (Stephens) on eggs and larvae of the lepidopterous species Mamestra brassicae (L.) was investigated including the prey's influence on survival and development. The experiments were done at 20 ± 1°C and L:D = 16:8. C. carnea larvae were fed on eggs and first instar larvae of M. brassicae, respectively. In both cases the daily predation rate of C. carnea increased slowly during the two first instars and reached a peak in the third larval instar. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
3
13
0
1
Order By: Relevance
“…obs.). The results confirmed the more voracious nature of third instar lacewings compared to second instars as reported by others (Principi and Canard 1984;Klingen et al 1996;Silva et al 2002). Both instars of C. carnea showed a clear preference for P. brassicae caterpillars over eggs when both prey types were presented together.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…obs.). The results confirmed the more voracious nature of third instar lacewings compared to second instars as reported by others (Principi and Canard 1984;Klingen et al 1996;Silva et al 2002). Both instars of C. carnea showed a clear preference for P. brassicae caterpillars over eggs when both prey types were presented together.…”
Section: Discussionsupporting
confidence: 91%
“…Supportive evidence of the potential of C. carnea against lepidopteran pests comes from observations that this species could complete juvenile development when feeding on eggs of Mamestra brassicae (Linnaeus) (Lepidoptera: Noctuidae) or of Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) (Ş engonca and Grooterhorst 1985). Similarly, Klingen et al (1996) found that most C. carnea in their experiments could develop to adulthood by feeding on eggs or larvae of M. brassicae.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the ways in which predator consumption rates are reported in the literature are inconsistent and can lead to confusion. Some studies consider prey killed as equivalent to prey consumed (Burke and Martin 1956, Simpson and Burkhardt 1960, Krishnamoorthy and Mani 1982, Balasubramani and Swamiappan 1994, others exclude partially eaten prey from their calculations (Samson andBlood 1980, Chen andLiu 2001), and only a few clearly distinguish between numbers of prey killed and amount of biomass consumed (Klingen et al 1996, Lucas et al 1997, Soares et al 2004). …”
Section: Figmentioning
confidence: 99%
“…Atributos como elevada capacidade de busca, alto potencial reprodutivo, capacidade de explorar habitats variados e ampla diversidade de presas (ALBUQUERQUE et al, 2001). Os crisopídeos alimentam-se de pulgões, cochonilhas, moscas-brancas, ovos e larvas de diversos outros insetos, além de vários artrópodes de pequeno tamanho e de tegumento mole (KLINGEN et al, 1996). O uso de crisopídeos como agente de controle biológico da traça-das-crucíferas Plutella xylostella (L.) (Lepidoptera: Plutellidae) pode ser uma alternativa eficiente em cultivos de repolho (TALEKAR & SHELTON, 1993).…”
Section: Introductionunclassified